Hippocampal Histomorphology and Biochemistry in Rats fed Diets containing Carbamazepine (African Journal of Biomedical Research, 2022)
In this study, the effects of carbamazepine on hippocampal histomorphology, acetylcholinesterase activity, and glutamate concentration in adult male Wistar rats were investigated.  Healthy Wistar rats of the male sex weighing between 200g-250g assigned randomly into 4 groups (n= 5) were utilized for this study. Group A received 2 mLs/Kg of distilled water, groups B, C and D received 160mg/kg, 120mg/kg, and 80mg/kg of carbamazepine. Carbamazepine was supplemented in rat chow for the study span of four weeks. The whole brain was harvested the following sacrifice fixed in 10% Neutral Buffered Formalin (NBF) and stained in H&E and Cresyl violet for hippocampal histomorphology and Nissl substances evaluation. Hippocampal Acetylcholinesterase (AChE) activity and concentration of glutamate were biochemically determined. Data obtained was analyzed using one-way ANOVA followed by Student Newman Keul posthoc test. A value of p